Plesiomonas shigelloides, an Atypical Enterobacterales with a Vibrio-Related Secondary Chromosome. (25th January 2022) - Adam, Yazid; Brezellec, Pierre; Espinosa, Elena; Besombes, Amelie; Naquin, Delphine; Paly, Evelyne; Possoz, Christophe; van Dijk, Erwin; Barre, Francois-Xavier; Ferat, Jean-Luc
Abstract: About 10% of bacteria have a multichromosome genome with a primary replicon of bacterial origin, called the chromosome, and other replicons of plasmid origin, the chromids. Studies on multichromosome bacteria revealed potential points of coordination between the replication/segregation of chromids and the progression of the cell cycle. For example, replication of the chromid of Vibrionales (called Chr2) is initiated upon duplication of a sequence carried by the primary chromosome (called Chr1), in such a way that replication of both replicons is completed synchronously. Also, Chr2 uses the Chr1 as a scaffold for its partition in the daughter cells. How many of the features detected so far are required for the proper integration of a secondary chromosome in the cell cycle? How many more features remain to be discovered? We hypothesized that critical features for the integration of the replication/segregation of a given chromid within the cell cycle program would be conserved independently of the species in which the chromid has settled. Hence, we searched for a chromid related to that found in Vibrionales outside of this order. We identified one in Plesiomonas shigelloides, an aquatic and pathogenic enterobacterium that diverged early within the clade of Enterobacterales. Our results suggest that the chromids present in P. shigelloides and Vibrionales derive from a common ancestor. We initiated in silico genomic and proteomic comparative analyses of P. shigelloides, Vibrionales, and Enterobacterales that enabled us to establish a list of features likely involved in the maintenance of the chromid within the host cell cycle.